Democratic legitimacy in global platform governance - Haggart, Blayne; Iglesias Keller, Clara (Telecommunications policy, 2021)
The goal of this paper is to propose a democratic legitimacy framework for evaluating platform-goverance proposals, and in doing so clarify terms of debate in this area, allowing for more nuanced policy assessments. It applies a democratic legitimacy framework originally created to assess the European Union's democratic bona fides – Vivian Schmidt's (2013) modification of Scharpf's (1999) well-known taxonomy of forms of democratic legitimacy – to various representative platform governance proposals and policies. The first section discusses briefly the issue of legitimacy in internet and platform governance, while the second outlines our analytical framework. The second section describes the three forms of legitimacy that, according to this framework, are necessary for democratic legitimation: input, throughput and output legitimacy. The third section demonstrates our framework's utility by applying it to four paradigmatic proposals/regimes: Facebook's Oversight Board (self-governance regimes); adjudication-focused proposals such as the Manila Principles for Intermediary Liability (rule-of-law-focused regimes); the human-rights-focused framework proposed by then-UN Special Rapporteur on the promotion and protection of the right to freedom of opinion and expression; and the United Kingdom's Online Harms White Paper (domestic regime). Section four describes our four main findings regarding the case studies: non-state proposals seem to focus on throughput legitimacy; input legitimacy requirements are frequently under examined; state regulation is usually side-lined as a policy option; and output legitimacy is a limited standard to be adopted in supranational contexts. We conclude that only by considering legitimacy as a multifaceted phenomenon based in democratic accountability will it be possible to design platform-governance models that will not only stand the test of time, but will also be accepted by the people whose lives they affect.